Standardisation of wind turbine SCADA data for gearbox fault detection. Issue 18 (18th June 2019) - Ferguson, David; McDonald, Alasdair; Carroll, James; Lee, Hyunjoo
Abstract : This study presents a method of anomaly detection within a gearbox by way of standardising temperature data. Assessing measured parameters in isolation is not sufficient to detect faults within a wind turbine. This technique uses temperature, rotational speed, and generator torque to detect a bearing fault within the gearbox. Standardising data allows a parameter to be analysed which also takes into consideration the operating state of the wind turbine, therefore providing a more holistic view of the health of the wind turbine and component being monitored.